IL-36/IL-36R signaling promotes CD4+ T cell-dependent colitis via pro-inflammatory cytokine production - Maarouf, Maya; Kuczma, Michal; Denning, Timothy L. (Frontiers in Immunology, 2025)
BackgroundInflammatory bowel disease (IBD) is a multifactorial, chronic disease that affects approximately 1.5 million people in the United States. Several important factors are implicated in the pathogenesis of IBD, one factor being dysregulation of the immune system. This dysregulation results in the accumulation and stimulation of innate and adaptive immune cells, and subsequent release of soluble factors, including pro-inflammatory cytokines. One of these cytokines is a member of the IL-36 cytokine family, IL-36γ, which is overexpressed in human IBD and experimental models of colitis. In this study, we explored the role of IL-36γ in promoting CD4+ T cell activation and cytokine secretion.MethodsSpleens and lymph nodes were collected from wild-type and IFNγ-/- mice and were processed into cell suspensions to isolate naïve CD4+ T cells. Naïve CD4+ T cells were stimulated with IL-36 cytokines. IFNγ and TNFα were evaluated by ELISA using cell culture supernatants, and cell culture pellets were used to isolate RNA for qPCR. Naïve CD4+ T cells previously stimulated in the presence or absence of IL-36γ, from wild type (WT) or IFNγ-/- mice were transferred to Rag-/- mice to induce colitis. Fecal pellets were collected from mice during disease to analyze lipocalin (LCN2) levels from fecal supernatants. After euthanasia, colons, spleens, and mesenteric lymph nodes were harvested and processed into cell suspensions for intracellular cytokine staining.ResultsOur results demonstrate that IL-36γ stimulation of naive CD4+ T cells significantly induced IFNγ expression in vitro and was associated with augmented intestinal inflammation in vivo using the T cell transfer model of colitis. Using IFNγ-/- naive CD4+ T cells, we observed a dramatic decrease in the ability of these cells to produce TNFα. Moreover, the transfer of these cells to Rag-/- mice did not cause robust colitis.ConclusionThese data not only suggest that IL-36γ is a regulator of a pro-inflammatory cytokine network involving IFNγ and TNFα but also highlights the importance of targeting IL-36γ and IFNγ as therapeutic approaches. Our studies have broad implications in relation to targeting specific cytokines in human IBD.